MENDORONG PERTUMBUHAN USAHA MIKRO, KECIL, DAN MENENGAH DENGAN PROGRAM – PROGRAM BERBASIS KNOWLEDGE MANAGEMENT (Dinamika Ekonomi, 2008)
UMKM(Small Medium Micro Business) plays a very important role in Indonesia, especially in creating the job opportunity that is considered as a safety closure in the process of national economic recovery. Based on the significant role of the UMKM, there are many efforts done by either the government or the bank to empower the UMKM, but the targeted result is not achieved yet. The government has maintained several targets in empowering UMKM, in order to realize them some guidance regulations have been made and clarified in the development programs as mentioned in the RPJMN 2004 – 2009. The general targets to be achieved in encouraging the development of the growth of UMKM above are clarified in the following programs: The program of choosing the personality with commitment, the program of forming LKM (Micro Financial Foundation) that supports UMKM as the source of investment for UMKM. The co-operation program with Colleges as the source of research, the program of partnership with the modern retailer in opening the access for the markets of UMKM, andmapping of the potential business.Keywords: Micro Business, Small Business, Medium Business, Management Knowledge